A Study on the Moderator Role of Vendor Trustworthiness on the Effect of Perceived Usefulness and Ease of Use in Mobile Shopping on Purchasing Intention - Uyanık, Meziyet; GÜRLER, İbrahim (International Journal of Contemporary Economics and Administrative Sciences, 2022)
This study examines the effects of users' perceived usefulness and ease of use of mobile sites in their mobile purchasing processes on customer satisfaction and purchase intentions, according to users' perceived trustworthiness towards the vendor with the Technology Acceptance Model perspective. As a result of the analysis made with the data obtained through the survey from 460 active mobile shopping participants over 18, it was concluded that the perceived usefulness and perceived ease of use affect the participants' satisfaction with the mobile site. This satisfaction has a positive effect on the purchase intentions of the customers. In addition, it was concluded that the perceived trustworthiness of the vendor has a moderating effect on the effect of the satisfaction of the participants from the use of the mobile site on their purchase intention. The positive relationship between participants' satisfaction with mobile site usage and purchase intentions is stronger under conditions of higher perceived trustworthiness towards the vendor.